A highly selective 2′′-O-glycosyltransferase from Ziziphus jujuba and De novo biosynthesis of isovitexin 2′′-O-glucoside. Issue 15 (27th January 2022) - Zhang, Ya-Qun; Wang, Zi-Long; Chen, Zhuo; Jin, Zheng-Tong; Hasan, Aobulikasimu; Wang, Hai-Dong; Sun, Yu-Wei; Qiao, Xue; Wang, Yong; Ye, Min
Abstract : We report a novel 2′′- O -glycosyltransferase indicating a new biosynthetic pathway of flavonoid O -glycosyl- C -glycosides. Abstract : A novel and efficient 2′′- O -glycosyltransferase ZjOGT38 was identified from Ziziphus jujuba . It could regio-selectively glycosylate 2-hydroxyflavanone C -glycosides. ZjOGT38 allowed de novo biosynthesis of isovitexin 2′′- O -glucoside in E. coli .